Restriction on land ownership and its implications on property development in Malaysia - Awang, Adibah (1993)
The powers to impose conditions and restrictions on landownership in the country is governed by various laws and policies, the main law being the National Land Code (hereinafter referred to in its abbreaviated from as "NLC") i.e. a uniform land law applicable to all the eleven states in Peninsular Malaysia. Such restrictions are viewed in this paper as a discouraging factor to those who are engaged in property development and, also as a safeguard to the citizens of Malaysia who are without land. As the content of this paper is based on a study on land ownership in Johor Bahru, an area where property development has been in the highest graph since 1980's, therefore it may represents the other areas throughtout Malaysia which have experienced such development per se. Johor Bahru is the capital city of the state of Johor which is situated at the southern tip of Peninsular Malaysia. Its proximity to Singapore is one of the factors which has contributed to its rapid economic development especially in its property sector. The Johor Bharu property market have attracted the Singaporeans especially its residential and agricultural properties, as property prices there are cheaper by one third of the property prices in the Republic. As a result, property prices becomes out of reach for most of the citizens. The move to restrict foreign ownership of real properties recently, will have far reaching implications on the property industry as it is one of the major contributor to the continued buoyant growth of Malaysia. However, there is undoubtedly a need of achieving a balance between the importance of achieving its national development strategies on the one hand, and the need to safeguard local interests on the other. The writer seeks hereby seeks to give an overview of the various restrictions impose by laws and policies on land ownership and its implications on property in the country.